Design and Optimization of a Combi Boiler Heat Exchanger: A Cfd Based Approach - Aydin, Ahmet; Engin, Tahsin; Kilic, Serhan (Elsevier BV, 2024)
Heat exchangers are widely used in various fields, emphasizing the importance of efficiency and mass/dimensional improvements. Aluminum boiler heat exchangers play a crucial role in systems, where the natural gas-air fuel mixture is burned and heat transfer to water occurs. In such heat exchanger designs, the region where the air-gas mixture burns is referred to as the "combustion chamber," and the thermal energy produced is transferred to the circulating water in the body. In this study, it was aimed to improve the heat transfer per unit surface by using novel pin-fin geometries in DAIKIN NDJ 24 kW aluminum cast boiler heat exchanger, thus reducing and lightening the dimensions of the combi heat exchanger for the same thermal performance. This approach targets cost reduction in production and downsizing of the boiler dimensions for more compact units. Cleanability limit was also established, and a unique symmetric droplet model was optimized utilizing a Computational Fluid Dynamics (CFD) based Response Surface Methodology (RSM) approach. Predictions of thermal performance through CFD simulations were subsequently validated experimentally using test bench available at DAIKIN's facility in Sakarya, T & uuml;rkiye. The results demonstrated a remarkable of 14% reduction in the overall weight, which was achieved by shortening the combi boiler height by 26 mm, while preserving the same efficiency levels. This research underscores the potential of the innovative pin geometry and optimized droplet model to enhance the efficiency and performance of the heat exchanger, with implications for cost savings and improved manufacturing processes. Also the effect of the new pin-fin geometry on the condensation performance was investigated as a multiphase phenomenon for the first time in the international literature. The results showed an excellent agreement between predicted and measured performance data.